Structure Elucidation and Complete NMR Spectral Assignments of New Sesquiterpenes Isolated From Marine Derived Fungus Aspergillus sydowii-HB - Teng, Baorui (Magnetic resonance in chemistry : MRC, 2025)
© 2025 John Wiley & Sons Ltd.